Effect of poling temperature on piezoelectricity of CaZrO3-modified (K, Na)NbO3-based lead-free ceramics - Yao, Fang-Zhou; Wang, Ke; Jo, Wook; Lee, Jae-Shin; Li, Jing-Feng (Journal of applied physics, 2014)
Electrical poling is indispensable for endowing isotropic ferroelectric polycrystals with a net macroscopic polarization and hence piezoelectricity. However, little attention has been paid to the optimization of poling conditions in (K, Na)NbO3-based ceramics with a polymorphic phase transition. This study investigated the electrical properties of CaZrO3-modified (K, Na, Li)(Nb, Ta)O3 lead-free piezoceramics as a function of the poling temperature. Peak piezoelectric coefficient d33 of 352 ± 7 pC/N and planar electromechanical coupling factor kp of 0.47 were obtained at the optimized poling temperature of 120 °C, which crosses the polymorphic phase transition regime. In-depth analysis of the asymmetric polarization hysteresis loops and bipolar strain curves uncovered striking analogy between electrical poling and unipolar cycling in the current system, which is attributed to a competition between domain reorientation and space charge accumulation.